MATERNAL AND NEONATAL OUTCOMES OF ADOLESCENT PREGNANCY AT A TERTIARY UNIVERSITY CLINIC - Aksam, Slavica; Dotlic, Jelena; Opalic, Jasna; Kocijancic Belovic, Dusica; Vukovic, Ivana; Bila, Jovan; Sparić, Radmila; Babovic, Ivana; Nikolic, Jovana; Sljivancanin, Dragisa (Medical Research, 2025)
Introduction/Aim: Pregnancy in adolescents increases the risk for numerous complications. The study aimed to investigate maternal and neonatal outcomes of adolescent pregnancies as well as the factors that can impact these outcomes. Materials and Methods: The Study included all viable singleton pregnancies of adolescent patients (14 to 19 years) and an equal number of adult patients (20 to 25 years) delivered during 2022 at the Clinic for Obstetrics and Gynecology, University Clinical Center of Serbia. We analyzed the patients’ age, comorbidities, parity, pregnancy controls, gestational complications, mode of delivery, complications during delivery, and in the early postpartum period, as well as the week of gestation at delivery, gender, birth weight, and Apgar score of newborns, and neonatal intensive care use. Results: The Study included 234 patients (117 adolescents and 117 adults). The majority of patients from both groups did not have any comorbidities or gestational complications. Adolescent patients control their pregnancy less often. Spontaneous vaginal deliveries were more frequent among adolescents. Apart from obstetric ruptures (30%), delivery complications were rare in both groups. Adolescents had preterm deliveries more often than adults. Nevertheless, almost all the children were born alive and healthy, regardless of the maternal age. Children of adolescents spent more time in intensive care. Regression analysis revealed that different parameters influenced the outcomes of adolescent and adult patients, while neonatal outcomes had the same predictors. Conclusion: Most of our adolescents do not regularly control their pregnancies. However, pregnancy complications in adolescents are not frequent.